A Review of Forest Fires: Causes, Impacts, and Management Strategies - Kumar, K. Praveen; Chintala, Radhika Rani (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This comprehensive review delves into the multifaceted realm of forest fires, exploring their diverse causes, far-reaching impacts, and the array of strategies employed for effective management. Beginning with an examination of the origins of forest fires, we scrutinize both natural and human-induced factors, providing a nuanced understanding of the intricate interplay that leads to ignition. The subsequent section explores the extensive ecological, environmental, and socio-economic impacts of forest fires, shedding light on their implications for biodiversity, air quality, and human communities. Moving beyond the analysis of causation and impact, the review meticulously surveys contemporary and innovative management strategies employed to mitigate and control forest fires. We assess the effectiveness of traditional approaches alongside emerging technologies, such as satellite monitoring, artificial intelligence, and community-based initiatives. Additionally, the review scrutinizes the role of prescribed burning, fire-resistant landscapes, and international collaboration in shaping successful management paradigms. By synthesizing current research findings and drawing on a diverse range of perspectives, this review aims to contribute to a holistic understanding of forest fires. Ultimately, it provides a valuable resource for policymakers, environmentalists, researchers, and the broader community working towards sustainable and resilient ecosystems in the face of this pressing global challenge.